Optomechanical Wagon‐Wheel Effects for Bidirectional Sorting of Dielectric Nanoparticles. Issue 6 (29th April 2021) - Xu, Xiaohao; Yang, Yi; Chen, Lixiang; Chen, Xixi; Wu, Tianli; Li, Yuchao; Liu, Xiaoshuai; Zhang, Yao; Li, Baojun
Abstract: The visual perception of a moving target is not always true. Wheels turning rapidly, for instance, may look like rotating inversely. This phenomenon is known as the wagon‐wheel effect (WWE) and it is caused by the undersampling of visual information. Here, an analogous manifestation of the WWE concept is described in the scenario of light–matter interactions, by showing that the dynamic response of a particle, to an optical trap scanned at different rates, can be diametrically opposed. Further, such behaviors are modulated by the particle dimensions, which can be exploited for particle size selection. The results uncover a distinct paradigm of nontrivial optical manipulation and expand the bidirectional optical sorting range of dielectric particles to the sub‐200 nm scale. Abstract : An all‐optical method is presented for bidirectional sorting of low‐index dielectric nanoparticles, by using a rapidly scanned optical tweezer. The idea is inspired by the illusion phenomenon known as the wagon‐wheel effect. The rapid motion of the tweezer can be correctly felt by larger particles but "cheat" smaller particles into moving against the scanning direction.